Metastatic squamous cell carcinoma transformed from prostatic adenocarcinoma following androgen deprivation therapy: A case report with clinicopathologic and molecular findings. Issue 12 (6th July 2020) - Lau, Hubert D.; Clark, Melissa
Abstract: Squamous cell carcinoma (SCC) of the prostate is a rare and clinically aggressive entity that may arise de novo or through transformation of prostatic adenocarcinoma, typically following hormonal or radiation therapy. Confirmation of prostatic origin, especially when evaluating a metastatic focus, often requires correlation with clinical and imaging findings, as the morphologic and immunohistochemical features of SCC are not organ‐specific. Comprehensive genomic profiling (CGP) may provide additional information useful for confirming the primary site and for identifying potential targeted therapy options. CGP data may also contribute to our understanding of the molecular basis of squamous differentiation in prostatic malignancies. However, these data are limited, and to our knowledge, there are only three previously published cases of prostatic SCC with reported CGP findings. Herein, we report a case of metastatic keratinizing SCC diagnosed by core needle biopsy in a 68‐year‐old man with a history of prostatic adenocarcinoma status post radical prostatectomy and androgen deprivation therapy (ADT). NKX3.1 immunohistochemistry was negative. CGP was performed, and a TMPRSS2 ‐ ERG fusion, among other genetic alterations, was detected, supporting a diagnosis of metastatic SCC transformed from prostatic adenocarcinoma following ADT. This case supports the use of CGP or other molecular techniques not only to query potential targeted therapy options but also to refine the diagnosis and confirm the primary site of disease in cases with non‐specific morphologic and immunophenotypic features, such as SCC.